Combined Dietary Recommendations, Desmopressin, and Behavioral In-terventions May Be Effective First-Line Treatment in Resolution of Enuresis - Ferrara, Pietro; Del Volgo, Valentina; Romano, Valerio; Scarpelli, Valentina; De Gara, Laura; Miggiano, Giacinto Abele Donato (Urology Journal, 2015)
Purpose: Nocturnal enuresis (NE) is a very common multifactorial pediatric disorder and in children without any other lower urinary tract symptoms is defined as monosymptomatic NE (MNE). Pharmacological, psychological/behavioral, and alternative interventions are commonly used and the first-line drug therapy for patients with MNE is desmopressin (dDAVP) but the response rate is less than 40-60% and the relapse rate is about 50-80% after treatment. Many studies show that some foods and beverages can promote diuresis or bladder irritability, which in some people can exacerbate bladder symptoms and NE. The present study aimed to compare the efficacy of combined specific dietary advices and dDAVP vs dDAVP alone. Materials and Methods: We enrolled in the study 172 patients affected by MNE between January 2013 and May 2014, of these 35 were excluded. The inclusion criterion was primary MNE and exclusion criteria included non-MNE, secondary MNE and lactose intolerance. Children were treated with dDAVP at a dose of 120 μg a day and were randomized to receive dietary recommendations. They were asked to fill out a charter depicting their wet and dry nights for the period of treatment. Sixty-seven patients were randomly assigned to receive dDAVP and dietary advices (group A) and 70 patients to receive dDAVP alone (group B). Results: We included in our study 137 children, 102 (74.5%) male, and 35 (25.5%) female, aged between 5 and 14 years. Our results show a higher response rate and a lower number of relapse in group A vs group B with 67.2% of responders in group A vs 58.6% in group B, after 3 months of therapy and 31.1% of relapse in group A vs 46.3% in group B one month, after the end of treatment. Conclusion: Our results show the effectiveness of specific dietary advices in the management of primary MNE. However further studies are needed to determine whether the difference between therapy with combined dietary recommendations and dDAVP vs dDAVP alone.